Gastric motility evaluated by electrogastrography and alternating current biosusceptometry in dogs - Andreis, Uilian [UNESP]; Americo, Madileine F.; Cora, Luciana A. [UNESP]; Oliveira, Ricardo B.; Baffa, Oswaldo; Miranda, Jose Ricardo A. [UNESP] (Iop Publishing Ltd, 2008)
Association techniques could be the answer for evaluating electromechanical coupling and gastric emptying under basal conditions and after administration of drugs. Electrogastrography (EGG) and alternating current biosusceptometry (ACB) emerged due to their interesting nature, noninvasiveness and low cost. The aims were to examine in dogs the effect of erythromycin on gastric emptying by ACB and electrical and motor responses to erythromycin and propranolol by ACB and EGG respectively. Twelve beagle dogs ingested a solid test meal on separate days. Under anesthesia, gastric motility was evaluated by EGG and ACB after erythromycin and propranolol administration. Without anesthesia, gastric emptying was assessed under basal conditions and after erythromycin by ACB. ACB and EGG showed a strong temporal correlation. Erythromycin and propranolol presented the same profile with different power ratios; the amplitude increased whereas frequency decreased. Also, erythromycin administration hastened gastric emptying while reducing the orocaecal transit time. There is a demand for reliable, easy-to-perform and comfortable techniques to record gastric emptying and gastric activity in medicine and veterinary practice. In summary, the association of ACB with EGG accompanied by an appropriate animal model is promising for evaluating effects of drugs in gastric myoelectrical and contractile activity.
Keywords: dogs; erythromycin; propranolol; gastric emptying; gastrointestinal motility